Light emission induced by an XUV laser pulse interacting resonantly with atomic hydrogen. (4th December 2015) - Li, Qingyi; Zhang, Zhiyuan; Zhang, Yunfeng; Li, Suyu; Fuming Guo; Yang, Yujun
Abstract: The resonant interaction between XUV ultra-short laser pulses and atomic hydrogen is systematically studied by numerically solving the time-dependent Schrödinger equation in this paper. Triple-peak structures are found to appear in the harmonics emitted provided that the incident laser is resonant with the 1 s-2p transition of the hydrogen atom. Moreover, the energy difference between neighboring peaks is the same and turns out to be proportional to the peak field strength E 0 . Based on the theory of strong field approximation, and taking the interactions of the 1 s-2p bound energy levels into consideration, theoretical interpretations of the phenomena mentioned are successfully presented. This work provides a possible approach for generating XUV radiation with a tunable frequency via the interaction between atoms and XUV laser pulses.